Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald, William C.; Philanthropie; Tabac; Université McGill

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Université McGill, Département de géographie, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

The (Spatialized) Hub-and-Spoke Industrial District Model: An Empirical Case Study of Montreal’s Aerospace Sector - Binkovitz, Isaac (Université McGill, 2009)
Keywords: Avionnerie

Industrial Land Retention in Two Cities: Municipal Strategies to Retain Manufacturing in Industrial Districts in Montreal and New York City - Charters, Stephen (Université McGill, 2011)
Keywords: Arrondissements; LaSalle; Le Sud-Ouest (arrondissement)

The Economics of Assembly and Transportation of Fluid Milk in the Montreal Area - Shipley, William Charlton (Université McGill, 1950)
Keywords: Lait

Modular Prefabrication versus Conventional Construction as a Cost Effective Alternative for the Construction of Single Family Detached Housing in the Montreal Area - Wiedemann, Stefan J. (Université McGill, 1990)
Keywords: Logement

Inter-Urban Industrial Linkages in Montreal's Hinterland - Murricane, Kenneth (Université McGill, 1975)

Made in Montreal: A Study of Geography and Priorities of Small Urban Manufacturers in Post-Industrial Montreal - Carruthers, Alex (Université McGill, 2012)

La relation entre l'évolution du salaire réel et de l'emploi: Montréal, 1963-1982 - Dagenais, Vincent (Université McGill, 1990)

For the Benefit of the Master: the Montreal Needle Trades During the Transition, 1820-1842 - Poutanen, Mary Anne (Université McGill, 1986)
Keywords: Apprentissage; Confection; Femmes

Le rôle des déterminismes sociaux dans le développement des forces productives de l'industrie textile du Canada, 1870 à 1910 - Ferland, Jacques (Université McGill, 1982)
Keywords: Textile

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

A Study of the Point St. Charles Shops of the Grand Trunk Railway in Montreal, 1880-1917 - Hoskins, Ralph F. H. (Université McGill, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

The Montreal Garment Industry, 1871-1901 - Payette-Daoust, Michelle (Université McGill, 1986)
Keywords: Confection

Industrial Location in the City of St. Laurent - Isenberg, Seymour (Université McGill, 1967)
Keywords: Saint-Laurent (ville)

Montreal Regional Industrial Pattern as Compared to that of Toronto - Fisher, David (Université McGill, 1940)

Industrial Land Use in Urban Areas with Special Reference to Montreal - Sharma, Brajesh Chander (Université McGill, 1971)

A Survey of Industrial Estates with Special Reference to Montreal - Grasser, Otto (Université McGill, 1964)

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

A Voice of English-Montreal. The First Twenty Years of Véhicule Press, 1973-1993 - Hemond, Amy (Université McGill, 2019)
Keywords: Imprimerie; Poésie; Édition